ANALISIS RISIKO KESEHATAN PAJANAN TIMBAL (Pb) PADA PEKERJA KAROSERI BUS ‘X’ di KOTA SEMARANG - Raisha Selviastuti; Yusniar Hanani Darundiati; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Carrosserie bus industry is the automotive industry engaged in the making of the chassis. During the production process, there is a health risk due to the use of hazardous materials during the work. The purpose of this study was to estimate the existence of occupational health risks occurs in the process of repainting due to exposure to lead in paint pigments. Place of carroserie buses this research is the “X” in the city of Semarang. The measurement of the concentration of lead in the air in five rooms painting process. Types of observational research with an environmental health risk analysis. Measurement of characteristics of anthropometry against 33 workers, which include weight loss, long exposure, frequency and duration of exposure. Health risks of noncancer Risk represented by Quotient (RQ) is obtained by dividing the average daily intake of noncancer throughout his life with the reference concentration (RfC), while the risk of cancer stated Excess Cancer Risk (ECR) obtained from estimates of between the daily intake of lifelong cancer with the cancer slope factor (CSF) lead. The results obtained lead concentrations that average concentration on space epoxy interior, epoxy primer (oven), epoxy components, stripping, and oven clear sequentially is 0,0008 mg/m3; 0,0008 mg/m3 ;0,0004 mg/m3 ;0,0077 mg/m3; dan 0,0003 mg/m3. With the concentration of lead and anthropometry as well as the characteristics of intake rate during the life time for workers “X” bus carrosserie obtained that the existence of the health risks they stripping noncancer (RQ >1) and cancer (ECR > 1 x 10-4). The conclusion of this study is a comparison of the value of health risk (RQ and ECR) on each part has the same tendency include the risk on the part of stripping > epoxy interior > epoxy primer (oven) > epoxy components > oven clear.